Perception of students toward St. Jude College. Inc., Manila S.Y. 2008-2009 : a study - Nicolas, Joyce N. (Manila : National University, 2009)
The purpose of this study was to perceptions of students towards the St. Jude College in School Year 2008-2009. The descriptive method of study was used.
Chapter 1. The problem and its background -- Chapter 2. Review of Related Literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation of data -- Chapter 5. Summary, Conclusions and Recommendations.
Includes bibliographical references.